TFRC promotes the proliferation, migration, and invasion of osteosarcoma cells by increasing the intracellular iron content and RRM2 expression - Ren, Guoqing; Zhou, Jian; Su, Yong; Yang, Qiang; Li, Jianmin (Frontiers in Oncology, 2025)
BackgroundMultiple studies have shown that the transferrin receptor (TFRC) is highly expressed in various tumors, and it has been recognized as a cancer biomarker. However, its role in osteosarcoma(OS) has rarely been studied. The purpose of this study was to explore the role and mechanism of TFRC in the proliferation, invasion, and migration of osteosarcoma cells.MethodsFirst, we analyzed the expression of TFRC in OS and normal cells with an open database and evaluated the correlation between TFRC expression and overall survival in OS patients. Quantitative real-time PCR (qRT–PCR), Western blotting, and immunohistochemical staining were used to determine the expression level of TFRC in OS cell lines and tissues. TFRC was knocked down by lentivirus-mediated short hairpin RNA (shRNA) in 143B and U2OS cells. The effects of TFRC knockdown on OS cell proliferation, migration, and invasion, as well as its mechanism related to ribonucleotide reductase M2 (RRM2), were explored through a series of experiments. Nude mice were inoculated with xenogeneic OS cells to study the influence of TFRC knockdown on tumor growth in vivo.ResultsTFRC was highly expressed in osteosarcoma, and its high level of expression was associated with poor overall survival in osteosarcoma patients. After TFRC was knocked down, the proliferation, migration and invasion ability of OS cells were significantly reduced, and TFRC knockdown effectively inhibited the growth of OS cells in xenograft experiments with nude mice. The knockdown of TFRC led to a decrease in the total intracellular iron content and a significant decrease in the protein expression of RRM2. The decrease in the proliferation, migration and invasion of osteosarcoma cells caused by TFRC knockdown was reversed by the addition of FAC or plasmids to overexpress RRM2.ConclusionOS cells regulate proliferation, migration, and invasion by overexpressing TFRC, which increases the transport of iron into cells and increases the expression and activity of RRM2.